Copshop [videorecording (DVD)] - Carnahan, Joe; Carnahan, Joe; Carnahan, Joe; Butler, Gerard, 1969-; Grillo, Frank, 1963-; Louder, Alexis (SDS, 2021)
To escape a hitman, a con artist gets himself arrested and locked up in a small-town police station, but soon the hitman schemes his way into a nearby cell, and then another hitman arrives.